Can subjective expectations data be used in choice models? Evidence on cognitive biases - Basit Zafar (Federal Reserve Bank of New York, 2010)
A pervasive concern with the use of subjective data in choice models is that the data are biased and endogenous. This paper examines the extent to which cognitive biases plague subjective data, specifically addressing 1) whether cognitive dissonance affects the reporting of beliefs, and 2) whether individuals exert sufficient mental effort when probed about their subjective beliefs. For this purpose, I collect a unique panel data set of Northwestern University undergraduates that contains their subjective expectations about outcomes specific to different majors in their choice set. I do not find evidence of cognitive biases systematically affecting the reporting of beliefs: By analyzing patterns of belief updating, I can rule out cognitive dissonance being a serious concern in the current setting. Moreover, there seems to be no systematic (nonclassical) measurement error in the reporting of beliefs. In the reported beliefs for the various majors, I find no systematic patterns in mental recall of previous responses or in the extent of rounding. Comparison of subjective beliefs with objective measures suggests that students have well-formed expectations. Overall, the results paint a favorable picture for the use of subjective expectations data in choice models.
Keywords: D8; I2; J1; J7; 330; College majors; expectations; cognitive biases; endogeneity; dissonance